INVESTIGATION OF TORSIONAL DEFLECTION AS AN UNDESIRED MOTION IN ATOMIC FORCE MICROSCOPY WITH SIDEWALL PROBE (Jurnal Teknologi (Sciences & Engineering), 2015)
In this paper an analytical model is presented for the Micro-Cantilever (MC) of Atomic Force Microscopy with Side Wall probe (AFM-SW) in the tapping excitation mode. In this model the couple motion of the MC is taken into account while the torsional motion is considered as an undesirable motion which is coupled with the vertical motion. To this end, the effect of several parameters, namely; probe mass, probe dislocation, sidewall extension length, and tip sample interaction force is investigated on the occurrence probability of torsional and vertical motions. It is found that the probe dislocation is the prerequisite factor of the undesired motion happening. For sake of validation, the analytical results are compared against the previously published results, and an excellent agreement is observed.